O trabalho das agências de fact-checking no combate à desinformação em meio à crise de saúde pública da pandemia de covid-19 - Vieira, Marcus Vinicius de Souza (2023)
The article has as its core the phenomenon of infodemic and its effects on the informational environment of Brazilian society in the midst of facing the covid-19 pandemic, at a time when the marks of post-truth are observed as a comprehensive sociocultural phenomenon. The objective is to understand the extent of the problem of misinformation about the pandemic in Brazil, through a content analysis of the work to check false messages, carried out by Brazilian fact-checking agencies: Aos Fatos, Lupa, AFP Checamos, Projeto Comprova and G1 Fact or Fake. For that, in addition to the bibliographical research, a documentary survey was also carried out of all checks published by the agencies between August 1st and October 31st, 2020. After collecting the data, a content analysis was carried out, in a quantitative and qualitative way, considering methodologically established categories of analysis. It was concluded that the agencies do work for which there is a lot of demand, covering different types of narrative formats and the classification seals play a significant role in consolidating checking agencies as a territory of truthful information. However, the lack of clarity in the definitions of truth that agencies take as a reference, the excessive number of seals used and the enormous amount of false information that needs to be checked are indicative of the need for more initiatives to combat disinformation and not just on the part of the journalistic field, so that there is an environment that encourages the exercise of the democratic right to information.